Kadaluwarsa pada Kasus Pemutusan Hubungan Kerja dalam Hukum Ketenagakerjaan - Brilian Lawyer; Gunardi (Syntax Literate, 2023)
Expiration is a condition where a time limit has passed for our right to be able to file a lawsuit. Therefore, when filing a case, time is an essential concern for every party who wants to file a lawsuit in court. Each legal issue has a different time. One problem that often occurs in employment is the Termination of Employment Relations. When someone experiences Termination of Employment Relations (PHK), there are several rights that a worker should obtain. Still, if the employer does not fulfill these rights, the worker can file a lawsuit at the Industrial Relations Court (PHI). When filing a case, a worker must pay attention to the period regulated in Article 82 of Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes. In practice, there are still inaccuracies in determining the expiration date in Termination of Employment (PHK) cases. This research aims to determine how the expiry date for Termination of Employment (PHK) cases is regulated in employment law. The research method used by researchers is normative research. Researchers will examine the problems raised by linking them to applicable laws and regulations. The conclusion is that there are still things that need to be corrected in using the legal basis in determining the expiration date in cases of termination of employment.